PENERAPAN MODEL PEMBELAJARAN COOPERATIVE INTGRATED READING AND COMPOSITION UNTUK MENINGKATKAN HASIL BELAJAR DI SMAN 14 MAROS - Wardihan, Sri Hardianti Rukmana; Syahid, Akhmad; Nengsih, Ratika; Mustamin; Wahab, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study discusses the application of the Cooperative Integrated Reading and Composition (CIRC) learning model in improving learning outcomes in the subjects of Islamic Religious Education and Character Education for class XII students of Kumer 1 at SMA Negeri 14 Maros. The purpose of this study is to describe the application of the CIRC learning model in improving student learning outcomes. This study uses Classroom Action Research (CAR) which is carried out in two cycles, where each cycle consists of two meetings. The research subjects are 30 class XII students of Kumer 1. Data collection techniques used include observation, interviews, tests, and documentation. The data analysis technique uses percentage calculations and average values ​​(mean) to determine the activity and completeness of student learning outcomes. The results of the study show that the application of the CIRC learning model is able to improve student learning outcomes in each cycle. In cycle I, the number of students who achieved completeness was 20 people with an average value of 74.6 which is in the